A new tool to measure approaches to supervision from the perspective of community health workers: A prospective, longitudinal, validation study in seven countries - Vallières, Frédérique; Hyland, Philip; McAuliffe, Eilish; Mahmud, Ilias; Tulloch, Olivia; Walker, Polly; Taegtmeyer, Miriam (BMC, 2022)
This article was published in the BMC Health Services Research [© The Author(s). 2018 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/) ] and the definite version is available at: https://doi.org/10.1186/s12913-018-3595-7 The Journal's website is at: https://bmchealthservres.biomedcentral.com/articles/10.1186/s12913-018-3595-7#citeas